Malignant hyperthermia in a regional facility: A case study - Catherine Kleidon (Journal of Perioperative Nursing)
Malignant hyperthermia (MH) is a rare hypermetabolic state that may be triggered by both anaesthesia and non-anaesthesia triggers. The main anaesthesia triggers for MH are the depolarising muscle relaxant suxamethonium and volatile anaesthetic gases. MH presents in several ways with not all clinical symptoms being required to make a diagnosis. Safe and efficient patient management of MH requires knowledge and understanding of this inherited disorder. The perioperative team need to be aware of the tasks that are required to manage this emergency. This case study will discuss a suspected episode of MH presenting in a patient late on Christmas Eve 2018 in a regional facility. Access to the reversal drug dantrolene provided an additional challenge. The increase in knowledge gained by nursing staff involved in the management of this crisis proved to be a significant learning curve for all involved. It is hoped that this paper will enable other perioperative nurses to benefit from this experience.